Evaluasi Pola Penggunaan Obat Tradisional dan Swamedikasi di Desa Bireuen Meunasah Blang - Muhammad Natsir Ilvira; Fahmi Irsan Nasution; Hanafis Sastra Winata; Bayu Irvia Satria; Ekawaty Suryani Mastari (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
The use of traditional medicine has long been integral to Indonesian society, offering affordable and accessible healthcare options. This study evaluates the patterns of traditional medicine use in Bireuen Meunasah Blang Village, focusing on respondent demographics, self-medication practices, and perceptions of affordability, effectiveness, and accessibility. Using a descriptive quantitative design, data were collected from 97 respondents aged 18–60 years through structured questionnaires. Results indicate that 54.6% of respondents demonstrate adequate use of traditional medicine, while 76.3% follow appropriate usage guidelines. Perceptions of cost and availability were predominantly positive, with 48.5% finding traditional medicines affordable and 70.1% familiar with their names. However, knowledge of side effects and sources of information remains limited. These findings underline the need for targeted public health education to enhance safe and informed self-medication practices with traditional medicines.